Current knowledge about Post-Polio Syndrome (PPS) - Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Wójcik, Magdalena; Boreński, Grzegorz; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: PPS appears at least 15 years after polio virus infection, followed by stabilization of the neurological condition. In the course of the disease, there are neurological, musculoskeletal and general symptoms. The aim of the study: The article focuses on the current knowledge about post-polio syndrome. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed, Google Scholar, ReaserchGate database was carried out using the following keywords: post-polio syndrome, poliovirus, poliomyelitis Description: There is no treatment that would cure PPS patients. However, interdisciplinary management focused on symptomatic treatment can significantly improve the quality of life of patients. One of the first solutions proposed to improve the clinical condition of patients with PSS was physical rehabilitation. In the treatment of post-polio syndrome, in addition to the use of non-pharmacological agents, therapy with the use of immunoglobulin infusions, the use of coenzyme Q10 or L-citrulline treatment has been introduced. Summary: Despite the fact that there is no specific treatment in PPS, it has been proven that non-pharmacological intervention (motor rehabilitation, lifestyle change, orthoses, respiratory assistance) has a beneficial effect on relieving the symptoms of the disease